Inter-trap tunneling in vanadium doped TiO2 sol-gel films. (July 2020) - Simeonov, S.; Szekeres, A.; Covei, M.; Spassov, D.; Kitin, G.; Predoana, L.; Calderon-Moreno, J.M.; Nicolescu, M.; Preda, S.; Stroescu, H.; Gartner, M.; Zaharescu, M.
Graphical abstract: Highlights: Sol-gel V doped (0.03–1.2 at. %) anatase TiO2 films are deposited on p-Si substrates. Eog values are within 3.3−2.94 eV showing a decrease with increasing the V content. The charge transport mechanism is non-conduction band electron transport In 77−300 K temperature range the electron transport is through inter-trap tunneling. Acceptor level concentration is in the order of 10 19  cm −3 . Abstract: Multilayered anatase TiO2 films doped with 0.03 and 1.2 at.% vanadium, deposited on p-type Si substrates by the sol-gel layer-by-layer method are studied to reveal the influence of doping on the electrical properties of the films. Undoped TiO2 and doped TiO2 :V films were incorporated in Metal-Insulator-Semiconductor structures and their current-voltage characteristics were measured and analyzed. The specific resistivity is in the order of 10 5 Ohm.cm, decreasing by increasing the electrical field, an evidence of the electron injection in these TiO2 and TiO2 :V films. The current through the films is non-conduction band current limited with trap charge via deep levels with energy distribution in the TiO2 bandgap . In the 77−300 K temperature range the current at high electric fields is carried out by the electron inter-trap tunneling in these TiO2 films.